Implementation of Distributed Database in Waste Bank Application Using NOSQL - Sugiarto; Setya Wijaya, Riko; Indah Harya, Gyska; Glory Mei Stephany, Sherafim (IJCONSIST JOURNALS, 2024)
This paper presents the implementation of a NoSQL-based distributed database for a waste bank application aimed at improving the efficiency, scalability, and reliability of waste management systems. Traditional relational databases often struggle with handling large volumes of transactional data in real-time, particularly in expanding waste bank networks. The proposed solution utilizes MongoDB to address these challenges by distributing data across multiple servers, ensuring enhanced performance and scalability. The study focuses on managing user information, waste deposit transactions, and real-time updates. Testing was conducted using real-world data from Indonesia, involving 500 users and 15,000 transactions. The system demonstrated strong scalability, processing up to 5,000 transactions per minute with an average response time of 50ms. Additionally, real-time updates were delivered with a latency of 100ms, maintaining high user engagement. Results show that the NoSQL-based system offers significant improvements in handling large datasets, ensuring data consistency, and maintaining system uptime of 99.8%. This approach is well-suited for modern waste bank applications, particularly in diverse environments like Indonesia.